Bayesian methods in health economics: uncertainty in health economic evaluation 3 - O'Hagan, Anthony (Henry Stewart Talks, 2009)
Bayesian statistics, Health economics, Cost-effectiveness, Incremental Cost-Effectiveness Ratio (ICER), EICER, Incremental Net Benefit (INB), Economic modelling, Efficacy, QALYs, Cost-Effectiveness Acceptability Curve (CEAC), Uncertainty in economic evaluation, Cost-effectiveness data
Reviewed at 2022/03/30